The use of non-smooth surfaces to control the wake of a high speed train. (October 2020) - Wang, Dongwei; Chen, Chunjun; Deng, Chao
To solve some problems caused by the wake of a high-speed train, the control process, especially the mechanism of the non-smooth surface for controlling the wake of a high-speed train, is studied by using the detached eddy simulation. The numerical simulation method is validated by using the data from a wind tunnel experiment reported in literature. To study the passive control of the wake, the non-smooth surface is arranged on the front surface and the side surface of the train, respectively. The changes of the vortex structure, velocity, and aerodynamic drag before and after the control are presented, and then the flow control mechanism of the non-smooth surface is explored in detail. The results show that by arranging the non-smooth surface on the front and side surface of the tail car, the vortex motion in the tail of the train can be slowed down and the influence region of the wake can be shortened. At the same time, the velocity fluctuation amplitude in the wake region of the train apparently decreases and the aerodynamic drag of the train decreases after the control.